Atmospheric dust accumulation on native and non-native species: effects on gas exchange parameters - González, Juan Antonio (2014)
Plants are continuously exposed to atmospheric particulate matter (dust), and their leaves are the main receptors of deposited dust. The objective of this study was to assess the effects of dust deposition on leaf gas exchange parameters of 17 native and non-native tree and shrub species growing in Gran San Miguel de Tucumán in northwestern Argentina. Maximum assimilation rate (Amax), stomatal conductance (gs ), transpiration rate (E), internal CO2 concentration (Ci ), and instantaneous water-use efficiency (WUE) were measured in cleaned leaves (CL) and dusted leaves (DL) of different species on November 2010, July 2011, and September 2011. In almost all studied species, gas exchange parameters were significantly affected by dust deposition. Values for Amax, E, and gs of DL were significantly reduced in 11, 12, and 14 species compared with CL. Morphological leaf traits seem to be related to Amax reduction. Indeed, Mespilus germanica L. and Mespilus germanica species with pubescent leaves and thick ribs showed the highest reduction percentages. Contrarily, Ci and WUE were increased in DL but were less responsive to dust deposition than other parameters. Increases of Ci and WUE were significant in 5 and 11 species, respectively. Correlation analyses between Amax/gs , Amax/E, and E/gs pairs showed significant positive linear correlations in CL and DL of many studied species, including small and tall plants. These results suggest that leaf stomatal factors and shade-induced effect by accumulated dust are primarily responsible for the observed reductions in photosynthesis rate of DL.